Corporate Governance, Big4 and Earnings Management - Suhadak, Suhadak; Nawari, Nanang; Wardhani, Dian Kusuma (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2022)
This study aims to examine the effect of internal corporate governance on earnings management with Big4 as the moderating variable. This study uses a quantitative method using secondary data in the form of financial and annual reports of companies conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange (IDX) from 2010 to 2017. Data obtained from www.idx.co.id and the website company official. Based on purposive sampling, the final sample was 251 observations. The results of this study contribute to the investment decision that it is necessary to be careful on shares that have just been IPO and a few years after. The results show that the implementation of internal governance in IPO companies has no effect on earnings management. In addition, the services of big4 auditors in IPO companies are not able to show better audit quality. So that investors do not need to consider these factors in investment decisions. Penelitian ini bertujuan untuk menguji pengaruh corporate governance internal terhadap manajemen laba dengan Big4 sebagai variable moderasi. Penelitian ini menggunakan metode kuantitati dengan menggunakan data sekunder yang berupa laporan keuangan dan tahunan perusahaan yang sedang melakukan Initial Public Offering (IPO) di BEI tahun 2010 sampai dengan 2017. Data diperoleh dari www.idx.co.id dan website resmi perusahaan. Berdasarkan purposive sampling diperoleh sampel akhir sebesar 251 observasi. Hasil penelitian ini memberikan kontribusi pada keputusan investasi bahwa perlu berhati-hati pada saham yang baru IPO dan beberapa tahun setelahnya. Hasil menunjukkan bahwa penerapan tata kelola internal pada perusahaan IPO tidak berpengaruh terhadap manajemen laba. Selain itu, jasa auditor big4 pada perusahaan IPO tidak mampu menunjukkan kualitas audit yang lebih baik. Sehingga investor tidak perlu memEntingkan factor tersebut dalam keputusan investasi.